Standardised immunophenotypic analysis of myeloperoxidase in acute leukaemia. (7th November 2020) - Bras, Anne E.; Osmani, Zgjim; de Haas, Valerie; Jongen‐Lavrencic, Mojca; te Marvelde, Jeroen G.; Zwaan, C. Michel; Mejstrikova, Ester; Fernandez, Paula; Szczepanski, Tomasz; Orfao, Alberto; van Dongen, Jacques J. M.; van der Velden, Vincent H. J.
Summary: Given its myeloid‐restricted expression, myeloperoxidase (MPO) is typically used for lineage assignment (myeloid vs. lymphoid) during acute leukaemia (AL) diagnostics. In the present study, a robust flow cytometric definition for MPO positivity was established based on the standardised EuroFlow protocols, the standardised Acute Leukaemia Orientation Tube and 1734 multicentre AL cases (with confirmed assay stability). The best diagnostic performance was achieved by defining MPO positivity as ≥20% of the AL cells exceeding a lymphocyte‐based threshold. The methodology employed should be applicable to any form of standardised flow cytometry.